Effect of Endosperm Maturity Stages and Processing Methods on the Physicochemical Characteristics of Arenga Gum Powder Produced from Industrial Discarded Sugar Palm Endosperms - Jomduang, Somchai; Zainal Abidin, Nurul Fatin Syahirah (Food and Applied Bioscience Journal, 2018)
Sugar palm (Arenga westerhoutii Griffith) endosperms are processed into canned product in syrup. Some of the sugar palm endosperms (SPEP) that were discarded during sorting could be potentially used as texturizing agent because of their galactomannan content. The objectives of this study were to determine the physicochemical characteristics of discarded SPEP and the simplest processing methods for arenga gum powder production. It was found that all maturity stages (young, midmature, and mature) did not differ (p > 0.05) in glucose, fructose, mannose, and galactose content of SPEP. Mature SPEP showed the hardest texture (12,868.11 ± 7284.4 g.force) compared to young and mid-mature endosperms. Among the four processing methods, crushing the mature endosperms before drying was the simplest, as it was a noncomplicated method with the highest production yield (15.02 ± 0.59%). In addition, it was found that higher drying temperatures produced arenga gum with lower viscosity; 80 °C was the maximum critical drying temperature for arenga gum powder production with high viscosity. Arenga gum powder had similar functional properties to commercial guar gum in terms of water-holding capacity, oil-holding capacity, and water solubility. At room temperature, 2.75% (w/v) of the arenga gum had the same viscosity as recommended-concentration (1% w/v) commercial guar gum in food applications.